2012
DOI: 10.1186/1471-2458-12-912
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in risk factors for non communicable diseases in low-income and middle-income countries: results from the World Health Survey

Abstract: BackgroundMonitoring inequalities in non communicable disease risk factor prevalence can help to inform and target effective interventions. The prevalence of current daily smoking, low fruit and vegetable consumption, physical inactivity, and heavy episodic alcohol drinking were quantified and compared across wealth and education levels in low- and middle-income country groups.MethodsThis study included self-reported data from 232,056 adult participants in 48 countries, derived from the 2002–2004 World Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
154
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(195 citation statements)
references
References 30 publications
(31 reference statements)
21
154
2
6
Order By: Relevance
“…Our results are consistent with the developing nations' data on smoking among females [27]. We found that the prevalence of smoking was higher among first level primary or higher graduate women compared with their illiterate peers (OR=2.72; 95% CI=1.14-6.50) (p=0.025) ( Table 3).…”
Section: Definitionssupporting
confidence: 81%
“…Our results are consistent with the developing nations' data on smoking among females [27]. We found that the prevalence of smoking was higher among first level primary or higher graduate women compared with their illiterate peers (OR=2.72; 95% CI=1.14-6.50) (p=0.025) ( Table 3).…”
Section: Definitionssupporting
confidence: 81%
“…Although chronic non-communicable diseases (NCD) are a matter of great public health concern worldwide, they affect developing countries more significantly (1) . In Brazil, NCD cause approximately 70 % of deaths and the prevalence of their main risk factors has shown an unfavourable tendency.…”
Section: Adolescent Health School Food Consumption Eating Behaviour Rmentioning
confidence: 99%
“…This is concerning, as a low level of literacy is one of the leading factors influencing unhealthy and risky behaviours. [40] As unemployment and alcohol and drug abuse are some of the most pressing social problems among youths in Diepsloot, [28] it is possible that young adults are least exposed to NCD information as they go out to look for money to be able to purchase alcohol and drugs. Hence, they are less likely to access services such as HIV testing and counselling, which also provide NCD-related knowledge.…”
Section: Researchmentioning
confidence: 99%